2014
DOI: 10.1039/c4ra10478a
|View full text |Cite
|
Sign up to set email alerts
|

Post-extrusion heat-treatment as a facile method to enhance the mechanical properties of extruded xylan-based polymeric materials

Abstract: Hemicelluloses are among the most abundant renewable polymers in nature, and their processing into biodegradable polymeric materials via extrusion was recently reported as a novel alternative technique for solvent casting. A simple heat-treatment step conducted after the extrusion of corn cob xylans was found to enhance the mechanical properties of strips by altering their moisture absorption behavior. Depending on the heat-treatment temperature, which varied between 60 C and 150 C, xylan-based strips with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…Although the vast majority of materials in the packaging industry are produced by thermal processing, research literature on hemicellulose‐based films is exclusively focused on casting techniques with a few exceptions. Heat treatments usually increase crystallinity of cellulose and produce crosslinking of lignin, which might improve the film forming and materials properties of carbohydrate‐based films. On the other hand, relatively high temperature treatments during thermal processing might reduce the molecular weight of the hemicellulosic components.…”
Section: Applications Of Plant Polysaccharide Materials In the Packagmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the vast majority of materials in the packaging industry are produced by thermal processing, research literature on hemicellulose‐based films is exclusively focused on casting techniques with a few exceptions. Heat treatments usually increase crystallinity of cellulose and produce crosslinking of lignin, which might improve the film forming and materials properties of carbohydrate‐based films. On the other hand, relatively high temperature treatments during thermal processing might reduce the molecular weight of the hemicellulosic components.…”
Section: Applications Of Plant Polysaccharide Materials In the Packagmentioning
confidence: 99%
“…On the other hand, relatively high temperature treatments during thermal processing might reduce the molecular weight of the hemicellulosic components. Recently, a study on the influence of different thermal treatments on corn cob extracted AX revealed interesting improvements in the materials properties of the films . The AX was extruded at 90°C, thermally annealed for 1 h at different temperatures and then conditioned for 7 days at room temperature and controlled humidity.…”
Section: Applications Of Plant Polysaccharide Materials In the Packagmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, all thermal modifications of wood at temperatures above 100 °C, but especially above 150 to 170 °C, cause certain changes in its chemical structure. These changes are reflected in changes in its properties (Kacikova et al 2013, Akkus et al 2014, Zawadzki et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…This interest aroused due to reduced production of durable wood material, an increased interest in durable construction material and legislative changes, which restrict the use of toxic substances. At present, the largest commercial importance is represented, in particular, by five different modifications, one in Finland, the Netherlands (Plato wood) and Germany (oil heat, OHT) [1]- [4].…”
Section: Introductionmentioning
confidence: 99%